Evaluation of the performance, operability, and safety of Plasauto μ, a new type of machine for cell‐free and concentrated ascites reinfusion therapy, in a postmarketing clinical study. Issue 4 (19th May 2021) - Hasegawa, Midori; Matsushita, Hiromichi; Yahata, Kensei; Sugawara, Akira; Ishibashi, Yoshitaka; Kawahara, Ryoko; Hamasaki, Yoshifumi; Kanno, Hitoshi; Yamada, Sachie; Nii, Norio; Kato, Masao; Ohashi, Atsushi; et al.
Abstract: Cell‐free and concentrated ascites reinfusion therapy (CART) is performed by collecting the ascites from the patient, followed by filtration and concentration. Thereafter, concentrated cell‐free ascites is reinfused into the patient intravenously. The new type of machine, Plasauto μ, for managing the process of CART was launched onto the market. We have evaluated the machine through postmarketing clinical study in 17 patients with malignant ascites. The amounts of original and concentrated ascites were 3673 ± 1920 g and 439 ± 228 g, respectively. Recovery rates were acceptable regarding values of total protein, albumin, and IgG that were 55.6% ± 17.3%, 60.2% ± 20.8%, and 58.2% ± 20.5%, respectively. Recovery rates were positively associated with amounts of original ascites and negatively associated with total protein concentration. No adverse events related to the machine were observed. The new type of machine showed preferable performance in processing malignant ascites.